Multivariate Water Stress Index Model for Predicting Water Vulnerability - Agustinus Haryanto Pattiraja; Srisanti LMF Seran; Hamdan Nurdin; Sulistiowati Sulistiowati; Stefanus G Engky Seran; Fransiska Adinda B Tokan (Journal La Multiapp, 2026)
Sabu Raijua Regency is a semi-arid island region with limited water resources and increasing water demand pressure, thus potentially experiencing high water vulnerability. This study aims to develop a multivariate Water Stress Index (WSI) model to analyze the dominant factors causing water stress and predict the level of water vulnerability in the medium to long term on Sabu Island. The study uses a predictive quantitative approach by combining multivariate regression analysis and spatial analysis based on Geographic Information Systems (GIS). The WSI value for the base year 2023 and the projection for 2033 were calculated using the Water to Availability (WTA) method which has been validated through the reliable discharge from the FJ Mock simulation results and field data. Eight independent variables were analyzed, including population density, water demand, dry spell and wet spell conditions, water availability, and clean water service coverage. The analysis results show that water demand (X3) is the most dominant factor in increasing the WSI value, while water availability (X7) plays a significant role in reducing water stress. Seasonal climate variables and clean water service coverage show relatively weak statistical effects. Spatial analysis identified West Sabu District as the area with the highest and persistent water stress, while Central Sabu and Sabu Liae Districts were at medium vulnerability levels, and Hawu Mehara and East Sabu were relatively lower.